Analysis of the Implementation of Ettawa Crossbred Goat Manure Treatment in the District Kulonprogo Yogyakarta, Indonesia - Kusumastuti, T A; Widiati, R; Nurtini, S; Paramitasari Syahlani, S; Ummul Muzayyanah, M A (KnE Life Sciences, 2019)
Livestock manure is a potential for soil fertility and increases the income of farmers. This research is to identify characteristic farmers and utilization of manure and the factors that influence the choice of farmers in carrying out manure treatment. The research was conducted in Kulon Progo Regency as a production center Ettawa Crossbred goats and taken one location the Village Ngargosari Samigaluh District of implementing mixed farming crops and livestock. The numbers of the sample were 65 respondents. The survey method was used to collect data using questionnaires to respondents. The data were analyzed quantitatively using Binomial Logistic Regression models. The results showed that the views of characteristic respondent had productive age (48.75 yr), have similar primary school education (51.00 %), business experience (22.63 yr) and dominance in the on-farm jobs (80.00 %). Average livestock ownership as much as 4.88 goats or 0:55UT. Utilization of manure for plants was 89.00 % and the remaining 11.00 % for fertilizer plants and sold. A total of 70.80 % of farmers did not do a manure treatment through fermentation. The independent variable number of livestock is the most influential factor positive and significance of the choice of farmers in implementing waste treatment (P < 0.05), the age of farmers positive and significant (P < 0.1), and the number of family members negative and significant (P < 0.1). This is due in goat raising is still dominated household. The implication of this research is the need for socialization understanding of the importance of manure treatment to improve the intangible benefits at the household of farmers. Keywords: Fermentation, Intangible benefit, Ettawa crossbred, Income, Manure treatment